Interplay of dietary antioxidants and gut microbiome in human health: What has been learnt thus far?. (January 2023) - Naliyadhara, Nikunj; Kumar, Aviral; Kumar Gangwar, Shailendra; Nair Devanarayanan, Thulsidharan; Hegde, Mangala; Alqahtani, Mohammed S.; Abbas, Mohamed; Sethi, Gautam; Kunnumakkara, Ajaikumar
Graphical abstract: A pictorial representation of positive (green shade) and negative (red shade) effects of different dietary antioxidants such as carotenoids, polyphenols, vitamin C, vitamin E, zinc, and selenium on the gut microbiota. Highlights: Dietary antioxidants play a vital role in maintaining human health. The action mechanism of antioxidants is highlighted. Food antioxidants regulate the gut microbiota homeostasis. Various clinical trials have shown a positive impact of dietary antioxidants on the gut microbiome. Abstract: The human gastrointestinal tract harbors a diverse range of microbial species, which helps to regulate various biological processes such as homeostasis of the gut barrier, stimulation of the immune system, and neurological health benefits from the gut-brain axis. Further, gut microbiome has been found to aid in the uptake of nutrients from food in large intestines. The dietary changes may lead to significant changes in the gut microbial population, which suggest that a positive change can be made in gut microbial diversity by changing the dietary style. The potential dietary substances that can positively enhance the gut microbial populations could be dietary antioxidants, which possess many health benefits in multiple oxidative stress-related diseases such as cardiovascular disease, cancer, diabetes, obesity, etc. Food antioxidants are necessary nutrients required by the human body to balance the oxidative stress generated from various biochemical and metabolic reactions. The interactions between the gut microbiota and antioxidants are vital for maintenance of homeostasis in gut microbiome, as it helps in the diversity of gut bacteria and influences the bioavailability of antioxidants by increasing the production of bioactive metabolites through microbiome. It is evident from different studies that food-derived antioxidants and gut microbial population have an active interaction leading to alleviation of gut microbial dysbiosis. A plethora of clinical studies has found the positive impact of food antioxidants on gut microflora that could aid in developing gut microbe-targeting therapeutics for various diseases. This review discusses the health benefits of major dietary antioxidant groups, and the interaction of gut microbiota with these dietary antioxidants in-depth with various pre-clinical and human dietary interventions.